Alarm Management Systems – Are You and Your Hospital Ready? - Yang, Rocky; Maloney, Maureen; Ramirez, Mario R.; Edwards, Helen; Morris, Garnett; Nero, Gary (CMBES Proceedings, 2016)
Patient generated monitor alarms have been a concern for health care providers for years. Initiatives to ensure that clinicians hear an alarm or a warning signal when a patient’s condition is deteriorating include: louder tones at the patients’ bedside with concomitant warning lights outside of the patient room; centralized monitoring of the patient’s conditions at the nursing station to name a few. Another initiative includes patient alarms generated at the bedside sent to dedicated pagers. Nursing personnel assigned to care for a monitored patient carry the pager and receive the alarms when their patient’s condition is deteriorating (complementary alarm notification). The Joint Commission on Hospital Accreditation published a Prepublication Standards document establishing alarm management as a 2014 National Patient Safety Goal*. The Safety goal was to be introduced in two phases culminating in the implementation of clinical alarm management policies and procedures by 2016. Manufacturers have developed systems that replace the older pager technology with smart phone technology, leveraging existing hospital’s infrastructure such as WIFI to transmit the alarm conditions. The presentation will describe the process that the Hospital followed in implementing an Alarm Management System, including our experience with the complexity of such systems that involve alarm management servers, smart phone technology, patient monitoring practices and ultimately using the WIFI infrastructure. It is our intention to provide some lessons learned so that other institutions can avoid some of the challenges associated with implementing such technologies. *Joint Commission Perspective, July 2013, Volume 33, Issue 7